B–N bond formation through palladium-catalyzed, microwave-assisted cross-coupling of nitrogen compounds with iodo-dodecaborate. Issue 78 (22nd September 2021) - Al-Joumhawy, Mahmoud K.; Marei, Tarek; Shmalko, Akim; Cendoya, Paula; La Borde, Jair; Gabel, Detlef
Abstract : A method is described which allows the synthesis of nitrogen-substituted hydridododecaborate clusters through Pd-catalyzed cross-coupling. Abstract : Substituted undecahydrido- closo -dodecaborates [B12 H11 NR2 ] 2− have potential use in materials and drugs, but have presented a synthetic challenge. Microwave-assisted palladium-catalyzed amination of iodo-dodecaborate [B12 H11 I] 2− allows mild and reproducible formation of B–N bonds with aromatic amines, HN-containing heteroaromatics, and amides. The reaction allows general access to amides, reproducible reactions to dodecaborate-substituted anilines, and, for the first time, the substitution of dodecaborate with HN-containing heterocycles.